Diseño arquitectónico de una terminal terrestre satélite situada en vía a la costa en la ciudad de Guayaquil - Cumba Jiménez, Israel Darío (2023)
Urban mobility is fundamental for the development of our societies, since it allows the integration of the inhabitants and to cover needs. The Project "Architectural design of a satellite land terminal located on the road to the coast in the city of Guayaquil" takes into account the existing needs of the place, due to the lack of adequate infrastructure for the transfer of passengers. Although there are terminals in the port metropolis, they are located far from the sector of study, the site is devoid of an adequate stop for users, being this a point of the city where traffic and pedestrian safety have become a problem, increasing the demand for private vehicles, a risk to the ecosystem and inclusion..........